HELLS Regulates Chromatin Remodeling and Epigenetic Silencing of Multiple Tumor Suppressor Genes in Human Hepatocellular Carcinoma - Law, Cheuk‐Ting; Wei, Lai; Tsang, Felice Ho‐Ching; Chan, Cerise Yuen‐Ki; Xu, Iris Ming‐Jing; Lai, Robin Kit‐Ho; Ho, Daniel Wai‐Hung; Lee, Joyce Man‐Fong; Wong, Carmen Chak‐Lui; Ng, Irene Oi‐Lin; Wong, Chun‐Ming (Hepatology (Baltimore, Md.), 2019)
Hepatocellular carcinoma (HCC) is the third most lethal cancer worldwide. Increasing evidence shows that epigenetic alterations play an important role in human carcinogenesis. Deregulation of DNA methylation and histone modifications have recently been characterized in HCC, but the significance of chromatin remodeling in liver carcinogenesis remains to be explored. In this study, by systematically analyzing the expression of chromatin remodeling genes in human HCCs, we found that helicase, lymphoid‐specific (HELLS), an SWI2/SNF2 chromatin remodeling enzyme, was remarkably overexpressed in HCC. Overexpression of HELLS correlated with more aggressive clinicopathological features and poorer patient prognosis compared to patients with lower HELLS expression. We further showed that up‐regulation of HELLS in HCC was conferred by hyperactivation of transcription factor specificity protein 1 (SP1). To investigate the functions of HELLS in HCC, we generated both gain‐of‐function and loss‐of‐function models by the CRISPR activation system, lentiviral short hairpin RNA, and the CRISPR/Cas9 genome editing system. We demonstrated that overexpression of HELLS augmented HCC cell proliferation and migration. In contrast, depletion of HELLS reduced HCC growth and metastasis both in vitro and in vivo. Moreover, inactivation of HELLS led to metabolic reprogramming and reversed the Warburg effect in HCC cells. Mechanistically, by integrating analysis of RNA sequencing and micrococcal nuclease sequencing, we revealed that overexpression of HELLS increased nucleosome occupancy, which obstructed the accessibility of enhancers and hindered formation of the nucleosome‐free region (NFR) at the transcription start site. Though this mechanism, up‐regulation of HELLS mediated epigenetic silencing of multiple tumor suppressor genes including E‐cadherin, FBP1, IGFBP3, XAF1 and CREB3L3 in HCC. Conclusion: Our data reveal that HELLS is a key epigenetic driver of HCC; by altering the nucleosome occupancy at the NFR and enhancer, HELLS epigenetically suppresses multiple tumor suppressor genes to promote HCC progression.